TRENDS AND PROSPECTS FOR THE DEVELOPMENT OF CREATIVE MANAGEMENT IN MODERN ORGANIZATIONS (Development Service Industry Management, 2024)
In the article, the subject of research is the aspects of improving the management systems of organizations. Namely, we are talking about such a modern trend as creative management, or, in other words, the application of non-standard, atypical, innovative solutions to increase the efficiency of management in modern organizations. On this basis, the purpose of the research is to generalize trends and determine the prospects for the development of creative management in modern organizations. The importance, necessity and advantages of active use of creative management tools by domestic enterprises are indicated. A set of guidelines and tasks corresponding to them, in terms of the application and improvement of creative management, which need to be taken into account in business, are outlined. Methods and approaches to the implementation of creative management tools in the practice of functioning and development of domestic enterprises in modern conditions, including instability caused by war, are summarized. According to the results of the analysis of modern practices regarding the application of creative management in the management systems of domestic enterprises, it was established that these issues have been sufficiently updated recently and still have not reached a sufficient level of development. Currently, the following approaches to creative management are used to varying degrees: the model of "Innovative creativity; "Creative and comfortable climate" model; the "Structural and Process Innovations" model; Stewart's model; "DIFI" model; the model of Amabail et al. From the point of view of creative management, the planning and implementation of measures for the creation and development of clusters is currently an objectively existing necessity, because it allows: to ensure the expanded reproduction of resource potential due to investments in promising areas of economic activity and their high efficiency based on synergistic effect and economy on the scale of activity; increase the volume of financial and economic activity and improve the market position of the enterprise through the improvement of product quality, optimization of costs and price policy as a result of ensuring system management of all stages of the technological process from procurement of products to the sale of goods to the final consumer; to improve the parameters of viability and economic security of business entities in general as a result of better access to resources and markets, diversification of activities and creation of proper prerequisites for further development.
Keywords: organization management; creative management; creativity; personnel management; adaptation; human capital